Program support matters: A systematic review on teacher- and school related contextual factors facilitating the implementation of social-emotional learning programs - Ulla, Triin; Poom-Valickis, Katrin (Frontiers in Education, 2023)
School- and teacher-related contextual factors are those that often influence the quality of social-emotional learning (SEL) program implementation, which in turn has an impact on student outcomes. The current paper was interested in (1) Which teacher- and school-related contextual factors have been operationalized in articles that focus on the relationship between implementation quality indicators 200 and contextual factors in SEL program implementation in schools? (2) Which contextual factors would demonstrate the highest frequency of statistically significant relationships with SEL program implementation quality indicators and could therefore be more essential for ensuring the program outcomes? Determining the more significant contextual factors would allow for more focused and better-informed teacher professional development for supporting students’ social and emotional skills, it can also be useful for hypothesis development for quasi- experimental research designs of SEL program implementation on the school level. A systematic literature search was conducted in seven electronic databases and resulted in an initial sample of 1,281 records and additional journal and citation sampling of 19 additional records. 20 articles met the final inclusion criteria for the study (19 quantitative and one mixed methods). Inductive content analysis and quantitative analysis were employed to map the variables and estimate the relative frequency of statistically significant relationships across studies. Four categories of contextual factors were revealed: program support, school, teacher, and student categories. The results of the study reveal the diversity in contextual factors studied across SEL program implantation quality and bolster the relevance of program support factors (modeling activities during coaching and teacher–coach working relationship) for ensuring implementation quality. A link between teacher burnout and program dosage was revealed. Student factors emerged as a separate contextual level in school, with special attention to student baseline self-regulation that may influence SEL program implementation quality.